Generation and validation of structurally defined antibody–siRNA conjugates. Issue 10 (29th April 2020) - Nanna, Alex R; Kel'in, Alexander V; Theile, Christopher; Pierson, Justin M; Voo, Zhi Xiang; Garg, Ashish; Nair, Jayaprakash K; Maier, Martin A; Fitzgerald, Kevin; Rader, Christoph
Abstract: Gene silencing by RNA interference (RNAi) has emerged as a powerful treatment strategy across a potentially broad range of diseases. Tailoring siRNAs to silence genes vital for cancer cell growth and function could be an effective treatment, but there are several challenges which must be overcome to enable their use as a therapeutic modality, among which efficient and selective delivery to cancer cells remains paramount. Attempts to use antibodies for siRNA delivery have been reported but these strategies use either nonspecific conjugation resulting in mixtures, or site-specific methods that require multiple steps, introduction of mutations, or use of enzymes. Here, we report a method to generate antibody–siRNA (1:2) conjugates (ARCs) that are structurally defined and easy to assemble. This ARC platform is based on engineered dual variable domain (DVD) antibodies containing a natural uniquely reactive lysine residue for site-specific conjugation to β-lactam linker-functionalized siRNA. The conjugation is efficient, does not compromise the affinity of the parental antibody, and utilizes chemically stabilized siRNA. For proof-of-concept, we generated DVD-ARCs targeting various cell surface antigens on multiple myeloma cells for the selective delivery of siRNA targeting β-catenin (CTNNB1). A set of BCMA-targeting DVD-ARCs at concentrations as low as 10 nM revealed significant CTNNB1 mRNA and protein knockdown.